Efektifitas Sistem Informasi Akuntansi Koperasi Di Indonesia Faktor Kemampuan Teknik Personal, Keterlibatan Pemakai, Pemanfaatan Teknologi, Usia Dan Tingkat Pendidikan - Fitri Nur Kaifa; Cris Kuntadi; Rachmat Pramukty (Student Scientific Creativity Journal, 2023)
The effectiveness of an accounting information system is an illustration of the extent to which the target is achieved from a set of resources that are regulated to collect, process and store electronic data, then turn it into useful information and provide the required information reports both in quality and time. This article reviews the factors that influence the effectiveness of cooperative accounting information systems in Indonesia, namely factors of personal technical ability, user involvement, use of technology, age and level of education, a literature study on human resource management. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) the personal technical ability factor influences the effectiveness of cooperative accounting information systems in Indonesia; 2) user involvement, technology utilization, age influence the effectiveness of cooperative accounting information systems in Indonesia; and 3) the level of education influences the effectiveness of cooperative accounting information systems in Indonesia.